GAMBARAN TINGKAT KECEMASAN PADA PASIEN PRE OPERASI DI RUMAH SAKIT UMUM DAERAH TGK. CHIK DITIRO SIGLI - Siti Dara Aulia; Murniati Murniati (Yakpermas Press, 2022)
Anxiety is an emotional state characterized by excessive worry about various events of daily life. The anxiety felt is difficult to control and is associated with somatic symptoms such as muscle tension, irritability, difficulty sleeping, and restlessness. Pre Operative is the period that begins when the decision to undergo surgery is made and ends when the patient is transferred to the operating table,in this phase, some preparations must beprepared by the patient before the operation is performed. This study aims to determine the picture of anxiety levels in preoperative patients of the Regional General Hospital Tgk. Chik Ditiro Sigli. This research method is descriptive, namely, to determine the picture of anxiety levels in preoperative patients at the Regional General Hospital Tgk. Chik Ditiro Sigli. This study used a cross-sectional design or design. Data are taken by conducting Zung Self-Rating Anxiety questionnaire measurements. The results showed that more than half of the respondents in this study were in the late adult category (54.2%), female (54.2%), had higher education (62.7%), had no previous treatment experience (60.2%), almost all respondents are in a low socio-economic level (90.4%), and the majority of respondents’ anxiety is normal (97.6%). In conclusion, of the 83 respondents, 97,6% of respondents did not experience anxiety (normal), and only 2.4% experienced anxiety, namely light.